Менување на организациската култура преку промовирање на вредности кои поттикнуваат тимско работење - Јованоска, Ана (Економски факултет, УКИМ, Скопје, 2018)
The organizational culture is very significant aspect of the organization, because it can be used as a tool for performance management and overall work of the company. Implementation and sustainability of the positive and cohesive organizational culture should be a main interest of every organization as one of the prerequisites of success. The theory part of this doctoral thesis is oriented towards analyzing the nature of organizational culture through understanding cultural differences, the characteristics and different types of organizational culture, analysis of the process for implementation and development of the organizational culure, as well as the role of the effective teams in the culture of the organization. The empirical research of this doctoral thesis refers to the impact of the demographic characteristics and the type of the organizational culture in the teamwork level of the organization. The goal is to determine whether the change in organizational culture through promotion of certain values can encourage teamwork, i.e. whether certain type of organizational culture is in positive correlation with the teamwork level in the organization. The results of the research demonstrate that demographic characteristics don’t determine the teamwork level in the organization, but the culture type does influence the teamwork level. More precisely, out of the four types of organizational cultures which are subject of this research, the results suggest that only clan culture has a positive effect on the teamwork in the organization.
Changing organizational culture by promoting values that encourage teamwork
Докторска дисертација одбранета во 2018 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубомир Дракулевски.
Keywords: organizational culture, values, team work